2018
DOI: 10.1002/adsu.201800084
|View full text |Cite
|
Sign up to set email alerts
|

Tetrasulfide‐Functionalized Mesoporous Silica on Nanowire Ring Resonators for Detection of Aqueous Lead, Pb(II)

Abstract: currently the methods of choice for very accurate and selective detection. [4] Competing and more compact methods are based on colorimetric [5] or fluorescence [6] assays, X-ray fluorescence, or protein binding assays and have made considerable progress, even though some still lack the selectivity or sensitivity required for water quality monitoring. In most countries, the concentration of lead in drinking water is not allowed to exceed 5-15 ppb, whereas levels exceeding 1 ppm have been reported in heavily con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Lead is a toxic widespread metal pollutant that represents an environmental health menace. , A particular health concern in recent years has been the amount of lead in drinking water, as lead can leach into tap water from lead containing pipes and solders. This has encouraged investigation for the development of more precise lead detectors in water and the design of more selective chelating molecules capable of sequestering lead from liquid media. Therefore, the understanding of the hydration features in aqueous solution of lead is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Lead is a toxic widespread metal pollutant that represents an environmental health menace. , A particular health concern in recent years has been the amount of lead in drinking water, as lead can leach into tap water from lead containing pipes and solders. This has encouraged investigation for the development of more precise lead detectors in water and the design of more selective chelating molecules capable of sequestering lead from liquid media. Therefore, the understanding of the hydration features in aqueous solution of lead is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25–29 ] However, the adsorption capacity of MSNs was a great limitation because there are no functional sites on MSNs surface. [ 30 ] It was reported that by grafting high‐density carboxyl groups onto the pore surface of MSNs and complexing with platinum atoms, the drug loading efficiency of MSNs can be greatly improved. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%